2015
DOI: 10.1111/nph.13614
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endophyte infection of ryegrass reprograms host metabolism and alters development

Abstract: Summary Beneficial associations between plants and microbes play an important role in both natural and agricultural ecosystems. For example, associations between fungi of the genus Epichloë, and cool‐season grasses are known for their ability to increase resistance to insect pests, fungal pathogens and drought. However, little is known about the molecular changes induced by endophyte infection.To study the impact of endophyte infection, we compared the expression profiles, based on RNA sequencing, of perennial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
167
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(187 citation statements)
references
References 78 publications
(129 reference statements)
15
167
1
Order By: Relevance
“…The preference documented, for the first time in domestic herbivores, in this study suggests that the endophyte may deter herbivores even when alkaloids do not cause an apparent toxic effect like those reported for similar symbiosis (e.g. synthesis of lignin, flavonoids and anthocyanins) (Rasmussen et al 2009;Dupont et al 2015), these mechanisms might also be responsible for these plants' reduced preference as they can reduce nutritional quality or alter tissue coloration. This reduced preference of domestic herbivores for infected plants could play an important role in the maintenance of the endophyte (Hern andez Agramonte & Semmartin 2016) as domestic grazing represents a major pressure in temperate systems (Oesterheld et al 1992).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The preference documented, for the first time in domestic herbivores, in this study suggests that the endophyte may deter herbivores even when alkaloids do not cause an apparent toxic effect like those reported for similar symbiosis (e.g. synthesis of lignin, flavonoids and anthocyanins) (Rasmussen et al 2009;Dupont et al 2015), these mechanisms might also be responsible for these plants' reduced preference as they can reduce nutritional quality or alter tissue coloration. This reduced preference of domestic herbivores for infected plants could play an important role in the maintenance of the endophyte (Hern andez Agramonte & Semmartin 2016) as domestic grazing represents a major pressure in temperate systems (Oesterheld et al 1992).…”
Section: Discussionsupporting
confidence: 66%
“…Annual Lolium sp. different silica absorption, flavonoid and volatile compound synthesis, lignin concentration) with potential impacts on herbivores' preference (Rasmussen et al 2008(Rasmussen et al , 2009Huitu et al 2014;Li et al 2014;Dupont et al 2015). These types of alkaloids have not been described as toxic for cattle, but they have been described as modifiers of the preference of rodents and arthropods for infected seeds and plants (Omacini et al 2001;Uchitel et al 2011;Ueno et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…During the host's vegetative phase, the fungal pathogen causes no distinctive symptoms, reminiscent of plant endophytes – organisms that colonize plant tissue without causing apparent disease. In endophytes it has been shown that – despite the lack of explicit infection symptoms – the presence of a second organism within the host and their mutual interaction can lead to distinct changes in the physiology, morphology and growth of the host plant (Latchs & Christensen, ; Varma et al ., ; Olejniczak & Lembicz, ; Dupont et al ., ; Larriba et al ., ; Rozpadek et al ., ). Stunted growth of head smut‐infected plants has been previously reported (Gallart et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the higher phenol concentration of the EI leaves may have contributed to the higher locust resistance of the host plants. Combined with the reduction of primary metabolites such as carbohydrates and amino acids, our results suggest that endophyte infection triggers reprogramming of the host metabolism, favoring secondary metabolism at a cost to primary metabolism (Dupont et al, 2015). …”
Section: Discussionmentioning
confidence: 88%